The impact of training and motivation on employee performance: Exploring the mediating role of organizational culture in enhancing workforce productivity for sustainable development - Tanto Gatot Sumarsono; Liliyana Meissy Usim Putri; Boge Triatmanto (Community Service for Sustainable Community Journal, 2025)
Background: This study examines the influence of training and motivation on employee performance through the mediating role of organizational culture. In today’s competitive business environment, fostering a strong organizational culture and motivating employees are essential for enhancing performance. Employee development through training and motivation plays a crucial role in shaping a productive and efficient workforce. Methods: A quantitative research design was employed, utilizing surveys to collect data from employees. Structural Equation Modeling (SEM) was used to analyze the relationships between training, motivation, organizational culture, and employee performance. The study also investigated the mediating role of organizational culture in linking training and motivation to performance. Findings: The results indicate that both training and motivation positively influence organizational culture. Well-structured and frequent training programs contribute to a strong organizational culture, which in turn enhances employee performance. Likewise, motivation that fulfills employees' physiological, safety, social, esteem, and self-actualization needs reinforces organizational culture. The findings confirm that organizational culture partially mediates the relationship between training, motivation, and employee performance, underscoring its critical role in the effective implementation of training and motivational strategies. Conclusion: Training, motivation, and organizational culture are key determinants of employee performance. A well-implemented training program and effective motivational strategies, supported by a robust organizational culture, significantly contribute to workforce productivity. These findings highlight the importance of organizational policies that promote continuous training, employee motivation, and cultural development to drive performance and align with broader organizational goals. Novelty/Originality: This study advances the understanding of how organizational culture mediates the impact of training and motivation on employee performance. By integrating these factors within a unified analytical framework, this research provides valuable insights for organizations seeking to optimize workforce potential and improve overall performance.